ChemInform Abstract: Palladium‐ and Ruthenium‐Catalyzed Cycloisomerization of Enynamides and Enynhydrazides: A Rapid Approach to Diverse Azacyclic Frameworks. Issue 4 (28th January 2014) - Walker, P. Ross; Campbell, Craig D.; Suleman, Abid; Carr, Greg; Anderson, Edward A.
Abstract A highly efficient, stereo‐ and regioselective method for the cycloisomerizations of readily prepared alkynyl amides is developed to furnish a wide range of products having the attractive azacyclic scaffold.